Pre-transplant testosterone and outcome of men after allogeneic stem cell transplantation - Radujković, Aleksandar; Kordelas, Lambros; Krzykalla, Julia; Benner, Axel; Schult, David; Majer-Lauterbach, Joshua; Beelen, Dietrich W.; Müller-Tidow, Carsten; Kasperk, Christian; Dreger, Peter; Luft, Thomas (Haematologica, 2020)
Testosterone is an important determinant of endothelial function and vascular health in men. As both factors play a role in mortality after allogeneic stem cell transplantation (alloSCT), we retrospectively evaluated the impact of pre-transplant testosterone levels on outcome in male patients undergoing alloSCT. In the discovery cohort (n=346), an impact on outcome was observed only in the subgroup of patients allografted for acute myeloid leukemia (AML) (n=176, hereafter termed ‘training cohort’). In the training cohort, lower pre-transplant testosterone levels were significantly associated with shorter overall survival (OS) [hazard ratio (HR) for a decrease of 100 ng/dL: 1.11, P=0.045]. This was based on a higher hazard of non-relapse mortality (NRM) (cause-specific HR: 1.25, P=0.013), but not relapse (cause-specific HR: 1.06, P=0.277) in the multivariable models. These findings were replicated in a confirmation cohort of 168 male patients allografted for AML in a different center (OS, HR: 1.15, P=0.012 and NRM, cause-specific HR: 1.23; P=0.008). Next, an optimized cut-off point for pre-transplant testosterone was derived from the training set and evaluated in the confirmation cohort. In multivariable models, low pre-transplant testosterone status (<250 ng/dL) was associated with worse OS (hazard ratio 1.95, P=0.021) and increased NRM (cause-specific HR 2.68, P=0.011) but not with relapse (cause-specific HR: 1.28, P=0.551). Our findings may provide a rationale for prospective studies on testosterone/androgen assessment and supplementation in male patients undergoing alloSCT for AML.